2000
DOI: 10.1029/1999gl005429
|View full text |Cite
|
Sign up to set email alerts
|

Mantle transition zone structure beneath Tanzania, east Africa

Abstract: Abstract.We apply a three-dimensional stacking method to receiver functions from the Tanzania

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
106
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 17 publications
18
106
3
1
Order By: Relevance
“…[12] A study of mantle transition zone discontinuities by Owens et al [2000] using receiver function stacks and the tomography model from Ritsema et al [1998] found evidence for a 30-40 km depression of the 410 km discontinuity, a result that was latter corroborated by Huerta et al…”
Section: Previous Seismic Studiessupporting
confidence: 63%
See 1 more Smart Citation
“…[12] A study of mantle transition zone discontinuities by Owens et al [2000] using receiver function stacks and the tomography model from Ritsema et al [1998] found evidence for a 30-40 km depression of the 410 km discontinuity, a result that was latter corroborated by Huerta et al…”
Section: Previous Seismic Studiessupporting
confidence: 63%
“…But the limited vertical resolution in these models makes it difficult to determine if the LWA extends into the mantle transition zone and connects to anomalous upper mantle structure beneath eastern Africa. Regional studies of upper mantle structure in eastern Africa, on the other hand, have imaged a LWA extending from shallow depths downward into the transition zone but have not been able to ascertain if the anomaly continues through the transition zone to connect with the superplume structure in the lower mantle [e.g., Ritsema et al, 1998;Owens et al, 2000;Weeraratne et al, 2003;Park and Nyblade, 2006;Huerta et al, 2009;Adams et al, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…The utility of most other phases is still more limited due to either interference or low signal-to-noise levels, although it is often used to augment teleseismic P data PP (e.g., Gurrola et al, 1994;Owens et al, 2000). Useful structural information has on occasion also been extracted from regional P (e.g., Park and Levin, 2001) and PKP (e.g., Park and Levin, 2000) using 'receiver function'-style approaches.…”
Section: Geometrical Preliminariesmentioning
confidence: 98%
“…Утонение переходного слоя в целом подтверждается антикорреляцией его верхней и нижней границы [Shen et al, 1998;Li et al, 2000Li et al, , 2003Owens et al, 2000;Hooft et al, 2003], хотя в некоторых регионах (например, в западной части Северной Америки) границы 410 и 660 км антикоррелиру-ются друг с другом не всегда [Houser et al, 2008].…”
Section: подлитосферные расплавные аномалииunclassified